Periostin Predicts All-Cause Mortality in Male but Not Female End-Stage Renal Disease Patients on Hemodialysis - Li, Xitong; Liu, Yvonne; Hocher, Johann-Georg; Chu, Chang; Reichetzeder, Christoph; Kalk, Philipp; Szakallova, Angelika; Chen, Xin; Krämer, Bernhard K; Tepel, Martin; Hocher, Berthold (Cardiorenal medicine, 2024)
INTRODUCTION: Periostin is a matricellular protein. Elevated serum concentrations of periostin have been reported in patients with various cardiovascular diseases, including heart failure. Patients with end-stage renal disease have a substantially increased risk for cardiovascular diseases. However, there is a lack of clinical studies to clarify the prognostic significance of systemic periostin on all-cause mortality in patients with end-stage renal disease on hemodialysis. METHODS: 313 stable end-stage renal disease patients were recruited and followed for 5 years concerning all-cause mortality. At baseline, we collected blood samples and clinical data. Serum periostin concentrations were measured using a certified ELISA. RESULTS: The optimal cut-off value for serum periostin regarding all-cause mortality, calculated through receiver operating characteristic analysis, was 777.5 pmol/L. Kaplan-Meier survival analysis using this cut-off value demonstrated that higher periostin concentrations are linked to higher all-cause mortality (log-rank test: p = 0.002). Subgroup analysis revealed that serum periostin concentrations only affected all-cause mortality in male but not in female patients (p = 0.002 in male patients and p = 0.474 in female patients). Multivariate Cox regression analyses, adjusted for confounding factors, likewise showed that elevated serum periostin concentrations were positively associated with all-cause mortality in male (p = 0.028) but not in female patients on hemodialysis (p = 0.313). CONCLUSION: Baseline serum periostin is an independent risk factor for all-cause mortality in male patients with chronic renal disease on hemodialysis.
Keywords: Kidney Failure, Chronic; Sex Factors; ROC Curve; Humans; lidé středního věku; Renal Dialysis; Female; rizikové faktory; periostin; Aged; Sex dependency; dialýza ledvin; Periostin; senioři; lidé; Biomarkers; Hemodialysis patients; All-cause mortality; sexuální faktory; Cell Adhesion Molecules; ženské pohlaví; chronické selhání ledvin; biologické markery; Kaplanův-Meierův odhad; Male; Middle Aged; molekuly buněčné adheze; prognóza; Cause of Death; Kaplan-Meier Estimate; příčina smrti; ROC křivka; mužské pohlaví; Prognosis; Risk Factors